Participation in the Comprehensive Primary Care Plus Initiative - Singh, Pragya (Ann Fam Med, 2020)
PURPOSE: Comprehensive Primary Care Plus (CPC+) is the largest test of primary care payment and delivery reform. This program aims to strengthen primary care via enhanced and alternative payment, data feedback, learning, and health information technology support for practice transformation for more than 3,000 practices. We analyzed participation rates and how CPC+ practices differ from other primary care practices in CPC+ regions. METHODS: We assembled a unique data set describing all US primary care practices and compared primary care practices in CPC+ regions, CPC+ applicants, and CPC+ participants. Among CPC+ participants, we compared across 2 model tracks. RESULTS: Of the primary care practices in CPC+ regions, 22% applied for CPC+ and 15% participated. Practices that applied to CPC+ were diverse, but they were generally larger, more sophisticated electronic health record users, more likely to be owned by a hospital or health system, more likely to have experience with transformation efforts, and more likely to be in urban areas than practices that did not apply. Applicants also generally served slightly healthier and more advantaged Medicare fee-for-service beneficiaries. Differences between practices that applied but did not join CPC+ and CPC+ participants were smaller yet systematic. CONCLUSIONS: Participants in CPC+ are diverse but not representative of all primary care practices, underscoring the need to further engage practices that are small, independent, in rural areas, and lack experience with practice and payment transformation models, as well as the need to extrapolate evaluation results carefully.